Surviving a Lawsuit Against a Counseling Program: Lessons Learned From Ward v. Wilbanks. (April 2014) - Dugger, Suzanne M.; Francis, Perry C.
<x xml:space="preserve">Abstract</x> This article features information about a lawsuit brought by a former student against Eastern Michigan University and its counseling program. In addition to describing the major elements of the lawsuit, the authors reflect on lessons learned and offer recommendations for other counseling programs.